2000
DOI: 10.1177/00238309000430040301
|View full text |Cite
|
Sign up to set email alerts
|

Q uantitative Characterizations of Speech Rhythm: Syllable-Timing in Singapore English

Abstract: British English and Singapore English are said to differ in rhythmic patterning. British English is commonly described as stress-timed, but Singapore English is claimed to be syllable-timed. In the present paper, we explore the acoustic nature of the suggested cross-varietal difference. In directly comparable samples from British English and Singapore English, two types of acoustic measurements were taken; we calculated a variability index reflecting changes in vowel length over utterances, and measurements re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(100 citation statements)
references
References 32 publications
0
72
0
2
Order By: Relevance
“…the Appendix from Daniele & Patel, 2013 for an example nPVI computation). Originally developed by phoneticians to show that "stress-timed" languages (British English, German, Dutch) had naturally higher nPVI values than "syllable-timed" languages (French, Spanish, Italian), Patel and Daniele (2003a) used the nPVI to show that a composer's native language directly influences the rhythms he/she writes (Grabe & Low, 2002;Low, Grabe, & Nolan, 2000;Ramus, 2002; for recent data on vocalic nPVI in English, German, Italian, and Spanish, see Arvaniti 2012, Figure 2b). Recent studies of the nPVI have begun to explore the variation of this statistic with respect to time and culture.…”
Section: Introductionmentioning
confidence: 99%
“…the Appendix from Daniele & Patel, 2013 for an example nPVI computation). Originally developed by phoneticians to show that "stress-timed" languages (British English, German, Dutch) had naturally higher nPVI values than "syllable-timed" languages (French, Spanish, Italian), Patel and Daniele (2003a) used the nPVI to show that a composer's native language directly influences the rhythms he/she writes (Grabe & Low, 2002;Low, Grabe, & Nolan, 2000;Ramus, 2002; for recent data on vocalic nPVI in English, German, Italian, and Spanish, see Arvaniti 2012, Figure 2b). Recent studies of the nPVI have begun to explore the variation of this statistic with respect to time and culture.…”
Section: Introductionmentioning
confidence: 99%
“…It thus seemed likely [16] VarcoC [17] VI [21] VarcoV [17] rPVI-C [19] PVI [18] nPVI-V [19] rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems that they are not so uniform to differentiate the non-native languages. Low, Grabe, and Nolan (2000) found nPVI rather than rPVI could differentiate Singapore English and British English. Stockmal, Markus, and Bond (2005) reported that ΔC and rPVI may significantly distinguish the language Latvian spoken by native speakers and by Russian Latvian learners of different proficiencies while %V, ΔV and nPVI showed no significant difference among these groups.…”
Section: Previous Empirical Studies On Rhythm Measurementsmentioning
confidence: 95%
“…Additionally, based on the observation that stressed and unstressed vowels in languages employing stress rhythm vary widely in duration whereas the durations of vowels in syllable rhythm languages vary less, Low, Grabe, and Nolan (2000) thus introduce Pairwise Variability Index (nPVI). Later, Grabe and Low (2002) Vol.…”
Section: Rhythm Measurementsmentioning
confidence: 99%